The Relationship between Learning Activeness and Student Learning Outcomes in Al-Qur'an Hadith Subject - Laili Rahmawati; Mahmudah Mahmudah; Tamjidnor Tamjidnor; Makherus Sholeh (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to determine whether there is a relationship between active learning and student learning outcomes in Al-Qur'an Hadith subject at MIS Al-Ashriyah Banjarmasin. This study uses a correlation research type with a quantitative approach. Data collection using observation sheets, interviews, questionnaires and documentation. Processing data using statistical analysis correlation test to determine the relationship between two variables and determine the correlation coefficient. Based on data processing with the help of SPSS version 26, a correlation coefficient of 0.588 was obtained with the number N = 37 at the 5% level of 0.325. The result showed that 0.588 > 0.325 or value of r-count more than r-table. It shows a correlation or relationship with the medium category between learning activity and student learning outcomes in Al-Qur'an Hadith subject MIS Al-Ashriyah Banjarmasin. This research hopes to spur enthusiasm to increase active learning to achieve the best learning results.